2022
DOI: 10.1093/clinchem/hvab280
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Sperm DNA Integrity by Mean Number of Sperm DNA Breaks Rather Than Sperm DNA Fragmentation Index

Abstract: BACKGROUND Sperm DNA integrity is crucial for normal fertilization, implantation, and embryo development. Several assays are available to assess sperm DNA fragmentation but are limited by high price, complicated processes and low accuracy. Additionally, the evaluation parameter cannot accurately show the degree of sperm DNA damage. METHODS We developed a secondary amplification detection system based on terminal deoxynucleoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Sperm DNA integrity is crucial for fertilization and the development of healthy offspring, and more and more studies have confirmed that sperm DNA damage is related to male infertility (Agarwal et al, 2020). Sperm DNA fragmentation index (DFI) can reflect the integrity of sperm DNA, and is used as an important indicator to evaluate semen quality (Malic Voncina et al, 2021;Yan et al, 2022). This study performed the bioinformatics analysis on the transcriptome data of human sperm with high DNA fragmentation and normal DNA fragmentation, and screened out differentially expressed RNAs.…”
Section: Introductionmentioning
confidence: 99%
“…Sperm DNA integrity is crucial for fertilization and the development of healthy offspring, and more and more studies have confirmed that sperm DNA damage is related to male infertility (Agarwal et al, 2020). Sperm DNA fragmentation index (DFI) can reflect the integrity of sperm DNA, and is used as an important indicator to evaluate semen quality (Malic Voncina et al, 2021;Yan et al, 2022). This study performed the bioinformatics analysis on the transcriptome data of human sperm with high DNA fragmentation and normal DNA fragmentation, and screened out differentially expressed RNAs.…”
Section: Introductionmentioning
confidence: 99%
“…Sperm DNA as a carrier of paternal genetic information, plays an important role in fertilization and embryonic development (48). Sperm DFI can reflect the integrity of sperm DNA and is an important indicator to assist in the evaluation of semen quality after the traditional semen analysis (3,4). Oguz et al compared the effects of two commonly used sperm preparation methods (swim-up and gradient technique) on sperm DFI through SCD method, and the result showed that gradient method has no statistically significant reduction in the DNA fragmented sperm rate after preparation as compared to basal rates (49).…”
Section: Discussionmentioning
confidence: 99%
“…Sperm DNA integrity is crucial for fertilization and the development of healthy offspring, and more and more reports emphasize the direct relationship between sperm DNA damage and male infertility (2). Sperm DFI can reflect the integrity of sperm DNA, and is an important indicator to assist in the evaluation of semen quality after the traditional semen analysis (3,4). With the continuous development of science and technology, many new technologies have been applied to the examination of sperm DFI in clinical practice, including the TUNEL (terminal deoxynucleotidyl transferase dUTP nick end labeling) assay, Comet assay, SCSA (sperm chromatin structure assay), SCD (sperm chromatin dispersion) test, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The Xiang group developed a straightforward strategy for the direct evaluation of sperm DNA integrity via the TdT amplification method. 25 Yi and co-workers proposed an electrochemical biosensor for the analysis of target SARS-CoV-2 RNA by combining the catalytic hairpin assembly and TdT amplification strategies. 26 Such direct and efficient isothermal amplification assay without any additional templates can offer a promising opportunity to achieve the ultrasensitive detection of trace DNA in a sophisticated matrix.…”
Section: Introductionmentioning
confidence: 99%